Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26 - 29, 2023, Los Angeles, California - Rathje, Ellen M.; Montoya, Brina; Wayne, Mark H. (GSP (Series) ;, 2023)
This is the fifth volume of six Geotechnical Special Publications (GSPs) containing papers from the 2023 Geo-Congress. It includes 59 peer-reviewed papers on topics related to geotechnical data analysis and computation, including: computational geotechnics; data and software for geotechnical engineering; data, remote sensing, and cloud computing; education for geotechnical engineering; and virtual/mixed reality.